Substituents effects on properties of perylene dyes for spectrum conversion film. (January 2023) - Kim, Wan Soo; Yoon, Hyo In; Lee, Jae Moon; Hwang, Tae Gyu; Kim, Hong Mo; Lee, Hyun Kyu; Kim, Suhyeon; Choi, Woo Jin; Kim, Jae Pil
Abstract: Three dyes have been synthesized which were suitable for red fluorescence spectrum conversion film (SCF) by introducing substituents with different volumes at bay positions of the perylene dye. Photophysical properties, optimized structures, and energy states of the synthesized dyes were investigated. Thermal stability of the dyes was also investigated by thermogravimetric analysis (TGA). Stokes shift and fluorescence quantum yields of the dyes in solution state increased as the volume of the bay position-substituents increased. We compared Stokes shift of each dye by comparing the structural difference between S0 and S1 states of each compound. We also investigated quenching constant (kq ) and molar volume of the dyes in solution state to verify the relation between the degree of intermolecular steric hindrance and the degree of aggregation caused quenching (ACQ). Lastly, PMMA films doped with the dyes were fabricated, and their photophysical properties were investigated. The photosynthesis rate and growth of lettuce were measured using the film doped with PI-TBPO, which showed the best properties among the dyes to prove the effectiveness of the synthesized dyes. Graphical abstract: Image 1 Highlights: Structural twisting of perylene main body between S0 state and S1 state was calculated for Stokes shift analysis. Stern-Volmer equation was adopted and quenching constant (kq ) was calculated for fluorescence quenching analysis. Compounds were fabricated to SCF, then lettuce yield was measured to check benefit of the compounds on agricultural industry.